Response of three species of Salix to different soil types and water content (Revista de Ciências Agroveterinárias, 2014)
This work aimed to study the response of tree willow species to different water soil contents. The experiment was conducted inside a greenhouse using a completely randomized design, in a factorial arrangement of 2 x 3 x 4 with four replicates. Biomass production of Salix x rubens, Salix viminalis and Salix smithiana was higher when the moisture retention capacity of the soil was close to 100%.
Keywords: Water; Soil; Willow.